EFFECT OF PLANT EXTRACTS ON THE TREATMENT OF PAINT INDUSTRY EFFLUENT - S.SHARMILA; L.JEYANTHI REBECCA; MD SADUZZAMAN (International Journal of Pharma and Bio Sciences, 2013)
Environmental pollution is a global crisis. Since huge investment is required for the effluent treatment plant, various industries release the effluent to the environment without treatment. This leads to adverse effect on the environment. In this study, low cost and highly available plant materials were chosen for the treatment of paint industry effluent. Leaves of Prosopis juliflora, Nymphaea ampla, Annona squamosa, Manilkara zapota and Moringa oleifera were soaked in different solvents such as methanol, ethanol, chloroform and benzene and their phytochemical constituents were extracted. These extracts were used for treating paint industry effluent collected from Nagalkeni village, Pallavaram, Chennai. Among all the extracts, Nymphae ampla had considerable reduction in chloride (169.96mg/l), sulphate (600mg/l), chromium(950mg/l) and nitrate (80mg/l). Ethanolic extracts of Prosopis juliflora reduced more TDS (209mg/l) present in effluent. Methanolic extract of Annona squamosa considerably reduced hardness (640mg/l) of waste water.